The Effect Of Profitability, Leverage And Sales Growth On Tax Avoidance With The Size Of The Company As A Moderation Variable - Sriyono Sriyono; Ronny Andesto (Dinasti Publisher, 2022)
Taxes are the embodiment of the largest contribution to the development of a country including Indonesia, on the other hand, many taxpayers, especially companies, consider taxes to be a burden that can reduce income, so there are still many taxpayers who try to carry out tax avoidance activities. The purpose of this study is to determine the effect of profitability, leverage and sales growth on tax avoidance with the size of the company as a moderation variable. In this study, tax avoidance was measured using the Effective Tax Rate. The samples used in this study came from consumer goods industry sector companies listed on the Indonesia Stock Exchange during the 2016-2019 period. The sampling in this study used the purposive sampling method and obtained 32 companies as samples. The analysis method used is multiple regression analysis with the help of eviews 12 software. From this study, results were obtained that showed profitability had a significant negative effect on tax avoidance. Meanwhile, leverage and sales growth have no effect on tax avoidance.This research also shows the results that the size of the company is able to strengthen the negative influence of the profitability relationship on tax avoidance, but the size of the company cannot moderate the relationship between leverage and sales growth against tax avoidance.